The Oil Price and Aggregate Economic Activity: Evidence from Canada - Zhang, Wenjing (Université d'Ottawa | University of Ottawa, 2018)
In recent years, Canada has become one of the largest oil exporters in the world. As a result, how the volatility of oil price links to the growth of Canadian economy has received more and more attention. In this paper, the transmission of linear and non-linear oil price shocks to the Canadian macroeconomy is evaluated in the light of the existing research results and the specific situation of Canada. This paper investigates the impact of oil price fluctuations on real GDP and other economic variables in Canada, using multivariate vector autoregressive (VAR) linear and nonlinear models. Both models consist of real oil price and real GDP as two major variables of interest as well as intermediate variables such as real effective exchange rate (REER), real wage, inflation, and short and long-term interest rates. The result of this paper suggests that the oil price has significant effects on many real economic variables, especially real GDP, REER and inflation. Furthermore, in the non-linear model, evidence shows that a drop in oil prices has a greater impact on real GDP than the rise in oil prices. In the short term, rise in oil prices has a positive effect on the economy. While in the long-run, the effect turns to be permanently negative.